1973
DOI: 10.1002/jsfa.2740240913
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of processed Saccharomyces cerevisiae, Scenedesmus obliquus and Spirulina platensis as measured by protein synthesis in vitro in rat skeletal muscle

Abstract: Rats were fed for six consecutivedaysonadiet containingtheproteinsourcesunder test at a protein level of 20%. Protein synthesis by skeletal muscle ribosomes was measured in vitro. Synthetic activity was estimated per unit ribosomal RNA and per g of wet weight of muscle. In separate experiments the nitrogen efficiency ratio (n.e.r.) of the protein sources was determined after 21 days feeding at a 10% protein level.As measured by protein synthesis the nutritional quality of lyophilised baker's yeast Saccharomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…It has been shown previously (von der Decken, 1967(von der Decken, , 1968(von der Decken, , 1969; von der Decken & Omstedt, 1970; Omstedt & von der Decken, 1972) that protein synthesis in skeletal muscle and in liver is increased after feeding with proteins during I d subsequent to 3 or 5 d of protein starvation. Refeeding with an adequate-protein diet after 12 weeks of protein restriction caused a partial recovery from hepatic lesions within 48 h (Enwonwu & Sreebny, 1971).…”
Section: I974mentioning
confidence: 91%
See 1 more Smart Citation
“…It has been shown previously (von der Decken, 1967(von der Decken, , 1968(von der Decken, , 1969; von der Decken & Omstedt, 1970; Omstedt & von der Decken, 1972) that protein synthesis in skeletal muscle and in liver is increased after feeding with proteins during I d subsequent to 3 or 5 d of protein starvation. Refeeding with an adequate-protein diet after 12 weeks of protein restriction caused a partial recovery from hepatic lesions within 48 h (Enwonwu & Sreebny, 1971).…”
Section: I974mentioning
confidence: 91%
“…There is a significant reduction in the protein turnover after giving rats a low-protein diet (Waterlow & Stephen, 1968). The ability of ribosomes to incorporate amino acids into protein in vitro is correlated with the biological value of the nitrogen sources (von der Decken & Omstedt, 1970, 1972Omstedt & von der Decken, 1972;Omstedt, von der Decken, Hedenskog & Mogren, 1973). In the present investigation dietary proteins were replaced by defined amino acid mixtures, which have the advantage that changes in their composition are easily made to suit the purpose of the investigation.…”
mentioning
confidence: 92%
“…The microalgae Scenedesmus obiiquus and Spiruiina piatensis were obtained from the Kohlenstoffbiologische Forschungsstation EV Dortmund (FRG).3. Details on conditions of cul ture and processing have been described previously [12], The composition of the complete amino acid mixture was that of whole egg [13]. When one amino acid was excluded, the corresponding amount of nitrogen was added in the form of glycine.…”
Section: Dietary Nitrogen Sourcesmentioning
confidence: 99%
“…Investigations dealing with intracellular protein metabolism have revealed that the activity level of protein synthesis in liver and skeletal muscle is deter mined by the quality of the dietary proteins [3][4][5][6][7][11][12][13]. In skeletal muscle, a positive correlation was obtained between the biological value of the dietary proteins and protein synthesis; but there can be discrepancies between protein synthesis and protein efficiency ratio determinations [7,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation